Unraveling transboundary water security in the arid Americas. Issue 8 (17th November 2018) - Albrecht, Tamee R.; Varady, Robert G.; Zuniga-Teran, Adriana A.; Gerlak, Andrea K.; Routson De Grenade, Rafael; Lutz-Ley, América; Martín, Facundo; Megdal, Sharon B.; Meza, Francisco; Ocampo Melgar, Diego; Pineda, Nicolás; Rojas, Facundo; et al.
ABSTRACT: Transboundary waters are characterized by diverse and complex socio-politico-economic obstacles to effective water management. We examine five distinct cases in the arid Americas – in locations from the US–Mexico border to the Andes mountains – employing water security as a conceptual prism to unravel the multiple and varied attributes of transboundary water challenges. We describe how borders complicate water security in arid regions and explore how institutional arrangements and practices – within and across jurisdictions – respond to these challenges. We find that institutional capacity is needed on multiple levels for effective water management, and institutions must be responsive and flexible to change.